Analisis Dampak Thrifting terhadap Perekonomian Pedagang Pakaian di Pasar Lasoani - Riska yanti; Monika Astria; Fadila Larasaty A.S; Hairun Nisah; Anny Asnita; Anisah Anisah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to examine the impact of thrifting on the economic condition of clothing traders in Pasar Lasoani, to identify the factors that make thrifting a threat to these traders, to find solutions that traders can implement in facing competition with thrifted products, and to understand the Islamic economic perspective on thrifting practices in Pasar Lasoani. This study uses a qualitative research method, which is intended to describe and explain events or phenomena occurring in the field and to present data systematically, factually, and accurately regarding the facts or phenomena observed. The data for this study were obtained through observation, interviews, and documentation. The thrifting phenomenon has had a significant impact on the economy of clothing traders in Pasar Lasoani. On the positive side, this trend has increased income for traders who sell thrifted items due to their affordable prices and attractive variety. However, on the negative side, thrifting reduces the competitiveness of new and local clothing traders, thereby creating economic imbalances in the market. The increase in secondhand clothing imports is also perceived as a threat to the demand for new products, especially due to the strong interest of young consumers in branded clothes at low prices. To improve competitiveness, new clothing traders need to implement strategies such as price adjustments, product quality improvement, utilization of digital marketing, and consumer education on the advantages of new clothing. From an Islamic economic perspective, the practice of thrifting is permissible as long as it fulfills the pillars and legal conditions of buying and selling, namely clarity of the product, mutual agreement on price, and absence of excessive gharar (uncertainty). According to the school of Imam Malik, this practice is valid if the existing gharar is minor, unavoidable, and conducted with honesty, fairness, and transparency. Therefore, thrifting transactions in Pasar Lasoani can be considered in line with the principles of sharia.